PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA DENGAN STRATEGI PREDICT-DISCUS-EXPLAIN-OBSERVE-DISCUS-EXPLAIN (PDEODE) UNTUK MEMINIMALISASI MISKONSEPSI SISWA SMP - Megawati, Megawati; Ibrahim, Muslimin; Haryono, Tjipto (Universitas Negeri Surabaya, 2017)
This research had aimed to develop a Natural Science Learning Material with PDEODE strategy to minimize misconceptions of Junior High School students on material structure and function of plant tissue. The learning instrument is developed by using 4-D model with a try out-design namely one group pre-test - post-test design. The lesson plan has been tried out to 25 students? of VIII-B class SMP Raden Rahmat Surabaya in the odd semester of 2016/2017 academic year. The data collection apply data validation, observation, achievement test, and questionnaire. The research data were analysed descriptively both qualitative and quantitative. The research findings were as follows: (1) The validity of the learning instrument which comprises Lesson Plan, Student Book, Student Worksheet, and a valid Identify Misconceptions Instrument; (2) The practicality of the learning instrument that can be found from: (a) the implementation of the lesson plans that is categorized as ?good?, (b) the students? activities and (3) The effectiveness of the learning instrument that was reviewed through: (a) the decrease misconception student from pretest to postest;; and (b) the response of students? . Based on the data analysis, it can be concluded that the Natural Science Learning Instrument based Predict-Discuss-Explain Observe-Discuss-Explain (PDEODE) strategy was feasible to minimize of misconceptions student?s Junior High School.